(untitled) (Journal of Educational Sciences, 2016)
The differences of the educational activity on the formation of patriotism and civic consciousness in the process of education and training among students in one of the universities of Almaty are investigated. Based on the analysis of regulatory documents, a classification of the activities on the themes and targets identified and fixed the main problems of weak involvement of students in university activities and the low efficiency of patriotic education. The author offers concrete steps according to the solution of the specified problems, in particular measures for creation of special pedagogical conditions, which include the University of policy emanating from the principle of universal participation by all departments and the faculty of the University of TA; conduct monitoring studies on the effectiveness of patriotic education of students; strengthening the scientific work of the University sector, in particular students’ scientific circles; including curriculum development issues relating patriotic and educational themes.